(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article is devoted to the study of the economic efficiency of GHG emissions from the use of energy in agriculture in the EU and the candidate country for accession - Ukraine. Using the abstract-logical method, the essence of the category "economic efficiency of greenhouse gas emissions" was clarified and an indicator for its assessment was proposed. By actual statistical data and the method of economic analysis, calculations of the economic efficiency of carbon dioxide emissions from the use of energy in agriculture of the EU member states and Ukraine were made. The key factor influencing the economic efficiency of GHG emissions from energy consumption in the agricultural sector was identified. Due to econometric method of approximation estimation and the Excel software package, the presence of a direct, high-density linear relationship between energy consumption and carbon dioxide emissions in agricultural production was established. By ranking method and comparative economic analysis, a threshold value of energy consumption per hectare of agricultural land was found, which corresponds to a relatively high value gross production per ton of carbon dioxide emissions among the studied countries. It was established that for the candidate country for joining the EU - Ukraine and for the two Baltic countries - Latvia and Estonia, in order to increase the level of economic efficiency of GHG emissions in terms of implementation the European Green Deal, it is worth paying primary attention to the growth of economic productivity. Also, due to graphical and tabular methods of processing statistical data, it was established that the use of environmentally friendly energy (in particular, electric energy) in the process of agricultural production is not a key factor affecting the economic efficiency of GHG emissions.